2021
DOI: 10.1177/15280837211034240
|View full text |Cite
|
Sign up to set email alerts
|

Electric heating behavior of flexible knitted fabrics comprising reduced graphene oxide, with emphasis on resistance temperature-sensitive behavior and decoupling of contact resistance

Abstract: Electric fabric heaters have demonstrated potential applications in a wide range of fields for medical electrothermal, human healthcare and athletic rehabilitation. Whereas, little attention has been paid to the resistance variations and the interface of electric heaters. Here, this paper focuses on the resistance temperature-sensitive behavior and interfacial electricity of reduced graphene oxide (RGO)/polyester (PET) fabrics, which are obatained through a facile and scalable dip-coating method. When a curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The relative resistance has a well linear relationship with temperature, and its resistance temperature coefficient (TCR) is −0.738 %/°C, indicating that the resistance change is caused by temperature change and capable of temperature sensing. In addition, the change of relative resistance is obvious and TCR is superior to our prior works reported about RGO paper, RGO fabric and Silver Nanowire fabric, 9,16,56 which is helpful for the use as temperature alarm. There are migrating electrons (e m ) in the graphite plane and jumping electrons (e h ) between the graphite layers.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The relative resistance has a well linear relationship with temperature, and its resistance temperature coefficient (TCR) is −0.738 %/°C, indicating that the resistance change is caused by temperature change and capable of temperature sensing. In addition, the change of relative resistance is obvious and TCR is superior to our prior works reported about RGO paper, RGO fabric and Silver Nanowire fabric, 9,16,56 which is helpful for the use as temperature alarm. There are migrating electrons (e m ) in the graphite plane and jumping electrons (e h ) between the graphite layers.…”
Section: Resultsmentioning
confidence: 79%
“…As a two-dimensional carbon nano material, Graphene has become quite popular owing to its excellent mechanical, electrical, thermal and optical properties. 912 Reduced Graphite Oxide (RGO) composed of multilayer graphene is usually prepared by chemical oxidation intercalation, which is widely considered as excellent wave-absorbing material, 9,13 sensing material 14 and green heating material 15,16 ascribed to remarkable characteristics of low density, unique conformability and high dielectric loss compared with the traditional materials, 17 as well as low cost and compared with the monolayer graphene. Wang et al prepared a porous cocoon-like reduced graphene oxide (RGO) by a simple and green reduction reaction using ascorbic acid as the reductant.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the characteristic peak of graphite is usually observed at about 2h ¼ 26 . 29,30 It can be seen from Figure 1(b) that there was a higher and narrower peak at 26 of the CNTF, which was similar to graphite. It indicated that the CNT had low crystallinity and smaller crystal grains.…”
Section: Characterization Of Basic Performance Of Cntfmentioning
confidence: 90%
“…[91][92] Apart from increasing the graphene content and thermal annealing, other methods to improve the heating performance include repeated coating cycles, [93] hot pressing, [93] optimising the structures of the heating elements, [94] etc. Hong et al [95] fabricated the rGO/PET fabrics through dip-coating, which reaches an equilibrium temperature of ≈89 °C within 20 s under 0.055 A current. In addition to heating ability, an opposite linear trend was found between the resistance and temperature of a rGO/PET heater, suggesting the temperature sensitivity of the textile.…”
Section: (7 Of 16)mentioning
confidence: 99%